RECENT FORAMINIFERAL COMMUNITIES IN MAKASSAR STRAIT - Ricky Rositasari (JOURNAL OF COASTAL DEVELOPMENT, 2010)
Makassar strait is the very unique waters, the bottom topography was steep and complex, the waters masswas also exceptional since Indonesian through flow carried flavor water from Pacific warm pool to the area.To describe the exceptional of Makassar Strait hydrological characteristics through recent foraminiferalcommunity structure as a proxy, Oceanographical Expedition in Makassar Strait was conducted in October2004. Research Vessel of Baruna Jaya VII was used to carry out the research activities. Sediment layers arean essential tool on recording hydrological information in such period of time, and each certain layerpreserved certain information as a bench mark data at a time period. The result shows that there are 5genera of planktonic foraminifera which generated a bulk in sediment surface. Deep chlorophyll maximum inoceanic region of Makassar Strait was prominent factor generated living planktonic foraminifera in researchlocation. Benthic community was formed by 164 species from 78 genera. Water depth was affected to benthicforaminiferal diversity, distribution and species diversity, which reveal that water depth was limiting factorto benthic foraminiferal assemblage. Uvigerinid was the important taxa which make up 46 to 57 % of thebenthic specimen, particularly in river input yield adjacent area. Uvigerina asperula may considered as anindicator of OMZ (Oxygen minimum zone) in Makassar Strait.